PI3Kα is essential for the recovery from Cre/tamoxifen cardiotoxicity and in myocardial insulin signalling but is not required for normal myocardial contractility in the adult heart. (24th January 2015) - McLean, Brent A.; Zhabyeyev, Pavel; Patel, Vaibhav B.; Basu, Ratnadeep; Parajuli, Nirmal; DesAulniers, Jessica; Murray, Allan G.; Kassiri, Zamaneh; Vanhaesebroeck, Bart; Oudit, Gavin Y.
Abstract: Aims: Genetic mouse models have yielded conflicting conclusions about the role of PI3Kα in heart physiology: specifically, the question of whether PI3Kα has a direct role in regulating myocardial contractility. This has led to concerns that PI3K inhibitors currently in clinical trials for cancer may potentiate cardiotoxicity. Here we seek to clarify the role of PI3Kα in normal heart physiology and investigate changes in related signalling pathways. Methods and results: Targeted deletion of PI3Kα and PI3Kβ in the heart with a tamoxifen-dependent Cre recombinase transgene caused transient heart dysfunction in all genotypes, but only PI3Kα deletion prevented functional recovery. Reduction in tamoxifen dosing allowed for maintained gene deletion without any cardiomyopathy, possibly through activation of survival signalling through the related ERK pathway. Similarly, mice with PI3Kα deletion induced by constitutively active Cre recombinase had normal heart function. Insulin-mediated activation of Akt, a marker of PI3Kα activity, was impaired with increased ERK1/2 activation in PI3Kα mutant hearts. Pharmacological inhibition of PI3Kα with BYL-719 also caused impaired insulin signalling in murine and human cardiomyocytes as well as in vivo in mice, with increased fasting blood glucose levels, but did not affect myocardial contractility as determined by echocardiography and invasive pressure–volume loop analysis. Conclusion: Our results show that PI3Kα does not directly regulate myocardial contractility, but is required for recovery from tamoxifen/Cre toxicity. The important role for PI3Kα in insulin signalling and recovery from tamoxifen/Cre toxicity justifies caution when using PI3Kα inhibitors in combination with other cardiovascular comorbidities and cardiotoxic compounds in cancer patients.